2013
DOI: 10.1002/jgrd.50441
|View full text |Cite
|
Sign up to set email alerts
|

Locating initial breakdown pulses using electric field change network

Abstract: [1] Initial breakdown pulses (IBPs) observed in the fast electric field change (E-change) at the beginning of intracloud (IC) and cloud-to-ground (CG) lightning flashes are located using a time-of-arrival technique called Position By Fast Antenna (PBFA) with data from a network of 10 E-change sensors located at Kennedy Space Center. Location errors, estimated using a Monte Carlo method, are usually less than 100 m for horizontal coordinates and several hundreds of meters for altitude, depending on distance to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
125
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 80 publications
(133 citation statements)
references
References 26 publications
(66 reference statements)
7
125
0
1
Order By: Relevance
“…Both Stolzenburg et al [2013a] and Karunarathne et al [2013] found that the initial negative leader of CG flashes moves negative charge downward.…”
Section: Overview Of Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Both Stolzenburg et al [2013a] and Karunarathne et al [2013] found that the initial negative leader of CG flashes moves negative charge downward.…”
Section: Overview Of Modelingmentioning
confidence: 99%
“…Stolzenburg et al [2013a] also showed that each luminosity burst was time correlated with a large-amplitude IBP, whose duration was typically 20-40 μs. Marshall et al [2013] used the array of E-change sensors described in Karunarathne et al [2013] and PBFA locations to study IBPs in IC flashes. Marshall et al [2013] interpreted that those IBPs were caused by a negative initial leader that moved upward from the top of the cloud's main negative charge and reached the bottom of the cloud's upper positive charge.…”
Section: 1002/2014jd021553mentioning
confidence: 99%
“…(Karunarathne et al [2013] give more complete descriptions of the instrumentation.) Flat-plate E-change antennas [e.g., Kitagawa and Brook, 1960] were operated from 10 locations across an area of about 70 km × 100 km.…”
Section: Data Sourcesmentioning
confidence: 99%
“…[] and Karunarathne et al . [] give more complete descriptions of the data acquisition.) During July and August 2011, we operated flat plate E‐change antennas [e.g., Kitagawa and Brook , ] around Kennedy Space Center (KSC) in Florida.…”
Section: Instrumentationmentioning
confidence: 99%